Oxidant and Antioxidant Effects of Gentisic Acid in a 177Lu-Labelled Methionine-Containing Minigastrin Analogue - Trindade, Victoria; Balter, Henia (Current Radiopharmaceuticals, 2020)
Background: The radiolabelling of receptor-binding peptides for therapy is a challenge since the peptide itself is exposed (during labelling, storage and transport) to radiation-induced damage, directly or indirectly, in aqueous solution. Hence, the use of radiostabilizers seems to be mandatory, especially in peptide molecules that contain radiation-sensitive amino acids. Objective: The aim of this study was to investigate the effect of two stabilizers, gentisic acid and methionine, to delve into how each of them affects the radiolabelling and stability of the minigastrin analogue [177Lu]Lu-DOTA-His-His-Glu-Ala-Tyr-Gly-Trp-Met-Asp-Phe-NH2 through the analysis of the 22 species distinguished over time by an optimized HPLC system. Methods: The stabilizers, in different combinations, were present from the beginning of the labelling process carried out at 96 °C for 15 min. The stability was studied for up to 7 days. Results: The unexpected selective oxidation of the methionine residue of the radiolabelled peptide, promoted by gentisic acid, led to studying the effect of pH, from 3.5 to 6.0, in the presence of only this stabilizer. A pH-dependent antioxidant behaviour was revealed, showing a decrease in peptide impurities but an increase in the selective oxidation as the pH was increased. Conclusion: The selective oxidation of the methionine residue could be induced by oxidizing species probably produced in the reaction between gentisic acid and free radicals of water, during the protection of the radiolabelled peptide from the attack of these harmful species. Therefore, the addition of methionine becomes necessary to effectively decrease this selective oxidation in the methioninecontaining peptide.
Keywords: methionine